(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Google Workspace for Education offers various tools that are believed to be beneficial for both educators and learners. This paper aims to review the benefits of core tools in Google Workspace for Education and employment of the tools in the context of teaching and learning English. The paper is hoped to bring a better understanding of the usability of the tools for English language educators to make use of in order to digitally transform their classroom effectively.